An improvement on the upper bounds of the partial derivatives of NURBS surfaces - Tian, Ye (2021)
The Non-Uniform Rational B-spline (NURBS) surface not only has the characteristics of the rational Bezier surface, but also has changeable knot vectors and weights, which can express the quadric surface accurately. In this paper, we investigated new bounds of the first-and second-order partial derivatives of NURBS surfaces. A pilot study was performed using inequality theorems and degree reduction of B-spline basis functions. Theoretical analysis provides simple forms of the new bounds. Numerical examples are performed to illustrate that our method has sharper bounds than the existing ones.